Peningkatan Kemampuan Bercerita melalui Media Rotasia pada Anak Didik Kelompok A1 TK Pamekar Budi Desa Candisari Kecamatan Mranggen Kabupaten Demak Semester 1 Tahun Pelajaran 2016/2017 - Istirokah Istirokah (Universitas PGRI Semarang, 2017)
Age 4 - 6 years is the golden age in the development of child's life. At this age, all the potential ability of children can be developed optimally. One of the abilities that need to be developed is the child's ability to understand and express expressive language (basic competence 3-11-4.11) with an image telling indicator. Researchers found that the ability of children in telling the picture has not grown in line with expectations is 15 children there are only 3 children who can tell the appropriate language, 5 children who dare to appear in front and 4 children with a loud enough voice. Seeing these conditions, researchers tried to improve it by using media rotasia. The research was conducted at TK Pamekar Budi Desa Candisari Mranggen District for 3 months from August to October 2016 and using 2 cycles. The aspects studied in this improvement activity is the courage of children telling stories in front of the class, the suitability of the story with the picture and the volume of the child's voice when telling a story. Cycle I, researchers make improvements with the media rotation to tell stories with the title